Developing the EFL Students’ Reading Comprehension By Employing Herringbone Technique - Yusuf, Yunisrina Qismullah; Fajrina, Dian; Sari, Irma (Institut Agama Islam Negeri Imam Bonjol Padang, 2016)
This research aims to find out whether Herringbone Technique can developEFL students’ reading comprehension or not, especially in finding the main idea and supporting details in a recount text. The literature notes that Herringbone is known to be one of the techniques that can helpstudents to find important information and main idea in a text by seeking for answers on six comprehension questions on a diagram, viewed such as a fish’s skeleton. The sample of this research was 30 second grade junior high school students. The researchers employed simple random sampling to choose the sample. It further used the quantitative experimental approach with the pre-experimental design in the form of one group pre-test-post-test design.Pre-test was given before treatments, while post-test was given after the students were taught reading by using the Herringbone Technique. Each pre-test and post-test consisted of ten questions. The statistical formulas were used to analyze the data from the students tests’ scores. The mean score of pre-test was 59 and the post-test was 76. Futhermore, the result of t-test was 10.15, while the critical value of 0.05 significant level was 2.045, with the degree of freedom of 29. Since t-test (10.15) was higher than t-table (2.045), this study concludes that this technique could increase the EFL students’ reading comprehension.Despite in practice the researchers found that this technique decreased the students’ efforts in note-taking, however it did not inhibited them in obtaining improved scores in their reading tests.